Students’ Reactions to Learning English as a Foreign Language at an Indonesian College - Suwartono, Tono; Hossain Khan, Mohammad Lookman; Akter, Mahmuda (International Journal of Psychosocial Rehabilitation, 2020)
--- The universities in Indonesia offer English as a foreign language classes. Learning English is useful in getting a good job and access to global knowledge. Teachers help students to achieve proper use of a language. This study aimed to identify the teaching style of EFL classroom and students reaction while learning English as a Foreign Language. Twelve students from the Language Development Centre, Universitas Muhammadiyah Purwokerto participated in this study and they were at the intermediate level of English instructions. The data was collected through a Google form questionnaire consisting of 14 statements. The Google form link was sent to students via WhatsApp. To analyse the data, the descriptive statistic was used. This study found that the teachers of the Language Development Centre could understand the different student level. They were organized and was able to motivate the students. The students enjoyed the English classroom and their teachers were friendly and patient while teaching English. However, the students did not comfortably understand the native English speakers’ words. They could understand the local teachers’ English better. This study suggested the use of questionnaire in the Indonesian language in any further research. The study results recommended more research on student anxiety to justify students' enjoyment in the learning process. Furthermore, it is necessary to examine classroom activities to know what makes learning fun, significant and pleasant for the students.